Improved synthetic-heterodyne Michelson interferometer vibrometer using phase and gain control feedback - Galeti, Jose Henrique [UNESP]; Kitano, Claudio [UNESP]; Connelly, Michael J. (Optical Soc Amer, 2015)
Synthetic-heterodyne demodulation is a useful technique for dynamic displacement and velocity measurement using interferometric sensors as it can provide an output signal which is immune to interferometric drift. With the advent of cost effective, high-speed real-time signal processing systems and software, processing of the complex signals encountered in interferometry has become more feasible. In conventional synthetic-heterodyne demodulation schemes, to obtain the dynamic displacement or vibration of the object under test requires knowledge of the interferometer visibility and also the argument of two Bessel functions. In this paper, a new synthetic-heterodyne demodulation method is described leading to an expression for the dynamic displacement and velocity of the object under test that is significantly less sensitive to the received optical power. In addition, the application of two independent phase and gain feedback loops is used to compensate for the nonideal gain and phase response of the anti-aliasing filter required for the signal acquisition of the received wideband interferometer signal. The efficacy of the improved system is demonstrated by measuring the displacement sensitivity frequency response and linearity of a Piezoelectric Mirror-Shifter (PMS) over a range of 200 Hz-9 kHz. In addition, the system is used to measure the response of the PMS to triangular and impulse type stimuli. The experimental results show excellent agreement with measurements taken using two independent industry standard calibration methods. (C)2015 Optical Society of America